Relationship of Sexual Violence to Depression in Female Students of Faculty of Medicine, Pelita Harapan University - Xaviera, Luqyana Ghina; Kristiani, Erna; Suryadinata, Neneng (Medicinus, 2023)
Background: Sexual violence can take many forms to anyone. The increase in the number of sexual violence against women in Indonesia is quite significant. These incidents are reported to occur frequently in women in young adulthood. These experiences can have long-term effects, one of which is depression. There are several studies that show an association between sexual violence and the incidence of depression. However, there has not been much quantitative research to look at the relationship on this matter in Indonesia, especially on female students. This study aims to understand the relationship between sexual violence and the incidence of depression in female students of the Faculty of Medicine, Universitas Pelita Harapan.Methods: This study use a cross-sectional study design. The data has been collected using questionnaires filled in by the respondents. This study involved 149 female students of the Faculty of Medicine, Pelita Harapan University. The results of the study were processed and statistically analyzed using SPSS 25.Result: Based on research data, there are 149 respondents from female students of the Faculty of Medicine, Universitas Pelita Harapan. with a mean age of 19.29 (SD = 1.086). The youngest age of the respondent is 17 years old and the oldest is 24 years old. A total of 55 respondents had experienced sexual violence. Based on the results of the Beck's Depression Inventory (BDI) questionnaire, 16% had mild depression, 9% had moderate depression, and 2% had severe depression. Chi-square test showed a significant relationship between experiences of sexual violence and the incidence of depression, with p <0.001.Conclusions: Sexual violence is related to the incidence of depression in female students of the Faculty of Medicine, Pelita Harapan University.